2015
DOI: 10.1097/brs.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels and 1-Year Fusion Outcomes in Elective Spine Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 25 publications
1
57
1
1
Order By: Relevance
“…44 Recent evidence suggests that vitamin D deficiency may be associated with less favorable surgical outcomes after spinal fusion procedures and increased risk of pseudoarthrosis. 39 Epidemiological studies showed a wider prevalence of vitamin D deficiency than initially thought. One study reported about 41.6% of the general American population was found to be vitamin D deficient.…”
Section: Vitamin D Levelsmentioning
confidence: 98%
See 2 more Smart Citations
“…44 Recent evidence suggests that vitamin D deficiency may be associated with less favorable surgical outcomes after spinal fusion procedures and increased risk of pseudoarthrosis. 39 Epidemiological studies showed a wider prevalence of vitamin D deficiency than initially thought. One study reported about 41.6% of the general American population was found to be vitamin D deficient.…”
Section: Vitamin D Levelsmentioning
confidence: 98%
“…Such a relationship between vitamin D status and fusion rates was also demonstrated by some previous studies. 39,50 Other studies also reported an influence of vitamin D status on clinical outcome measures. Ravindra et al 39 found that patients with vitamin D deficiency showed significantly higher rates of nonunion and longer mean time to fusion when compared with patients with normal levels.…”
Section: Vitamin D Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, vitamin D deficiency has been shown to be a prevalent issue that can adversely impact elective spine surgery. 6,37,38 Ravindra et al found that 30.0% of patients undergoing elective spine fusion surgery had vitamin D deficiency; Stoker et al similarly found that 27.0% of patients undergoing spine fusion surgery had vitamin D deficiency. 39,40 Subsequent studies have shown that vitamin D deficiency has a negative impact on spine fusion outcomes.…”
Section: Bone Fragility and Its Impact On Elective Spine Surgerymentioning
confidence: 99%
“…Ravindra et al showed that vitamin D deficiency was an independent predictor of nonunion and that the time to fusion in patients with vitamin D deficiency was significantly longer. 38 A literature review performed by Kerezoudis et al found that patients presenting with vitamin D deficiency achieved lower fusion rates and had higher rates of persistent low back pain following spinal fusion. 6 Kim found that functional outcome as measured by Oswestry Disability Index inversely correlated with baseline 25(OH) Vit D after spine surgery.…”
Section: Bone Fragility and Its Impact On Elective Spine Surgerymentioning
confidence: 99%